Physicochemical properties, sensory evaluation and storage stability of vitamin E fortified pink guava juice / Aishah Bujang … [et al.] - Bujang, Aishah; Abdullah, Noriham; Abdul Rashid, Norizzah; Mohd Soheh, Norahiza; Jailani, Fadhilah (Research Management Institute (RMI), 2012)
Pink guavas (Psidium guajava L.) are tropical, climateric fruits that are commonly grown in Malaysia for juice and puree production. These fruit are highly aromatic and rich in potassium, vitamin A and C. It is well known that guava fruit contains significantly more vitamin C than most citruses. Vitamin C is a powerful antioxidant and anti-inflammatory agent. Pink guavas also have a high level of lycopene, a carotenoid which is considered good for fighting free radicals. Currently, Sime Darby Golden Hope Foods and Beverages company is the single largest pink guava plantation in the world with over 500 hectares of the fruit grown in Sitiawan, Perak. It is the only pink guava plantation in Malaysia and the largest integrated facility in Asia. The fruit are hand-picked and processed into puree and hygienically packed into aseptic bags and sealed in steel drums for overseas export market or process into ready-to-drink juice in tetrapak packaging for local market. Normally, fruit juices are cloudy in appearance, have a lot of colloidal suspensions that are either preferred by some consumers or considered as unattractive to the others. The juice cloudiness is contributed by the presence of different components (cell wall fragments, cellular organelles, oil droplets, hesperidin crystals, pectin etc.) together with polydisperse distribution of particles sizes (Sentandrau et al., 2011). The colloidal particles in the juices also carry flavour substances and natural antioxidants such as carotenoids, lycopene etc. Sedimentation of juice due to the presence of pulp particles caused the separation problem in most fruit juices. Addition of stabilising agent and homogenisation process are conducted to reduce the particle size of the sediments hence preventing separation from occurring. The choice of stabilisers used is also important depending on the properties of the juices. Starch, pectin, arabic gum, carrageenan gum, guar gum and xanthan gum are commonly used as stabilising agents in beverages. Homogenisation technique using ultrasonic vibrations and high-pressure homogenisers are nowadays used to disintegrate large fat globules into a more stable, small and uniform fat globules size. Sonication process is more preferred in food industries because of reduced processing time, higher throughput and lower energy consumption (Cheng et al., 2007).